Penyuluhan Vaksinasi Dalam Persepktif Al-Qur’an - Wahyudi, Achmad; Jalaludin, Moh. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2022)
Vaccination is the administration of antigens from viruses or bacteria that can evoke the immune system of the human body or give a kind of mild infection. Vaccination is carried out because of a good benefit with the main objective being to prevent any damage or harm that will occur to each individual, so that the individual can be well-maintained, and if the individual is exposed to the virus, then his existence does not transmit to others based on body maintenance. and environment. This is also included in the category of an emergency problem because it is to protect the soul and avoid danger. The approach taken by the Indonesian Ulema Council is not only based on arguments, but also uses science and technology to test the validity of the vaccine, both in terms of benefits and harms. It is this approach that makes withdrawing the previous decision and giving a halal decision on vaccines that is viewed from an urgent need in accordance with Islamic law.